ANALISIS PROFITABILITAS DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR DI BEI - Santy, Santy; Siregar, Dian Lestari (LPPM Universitas Putera Batam, 2021)
Interested parties need to be on time in submitting financial reports because the benefits are still of high quality and do not expire and are used as material for consideration in decision making. However, there are still companies that do not submit financial reports on time. This study aims to determine the effect of profitability and liquidity on the timeliness of submitting financial statements of manufacturing companies listed on the IDX for the 2015-2019 period. The population is 80 companies with purposive sampling technique, so that the remaining 25 companies. The type of data used is secondary data in the form of financial reports obtained through the IDX website. The data analysis technique in this study is logistic regression analysis using SPSS 25. The results of this study can be seen in the regression coefficient test where profitability (ROA) has no significant effect on timeliness and liquidity (CR) has no significant effect on timeliness. It can also be seen from the simultaneous test that profitability (ROA) and liquidity (CR) simultaneously have no effect on timeliness.